POLITICAL OPPORTUNITY STRUCTURE AND THE SUCCESS OF TEMANGGUNG TOBACCO PEASANT RESISTANCE TOWARDS GOVERNMENT REGULATION 81/1999 - Syamsudin, Muhammad Hasan; Subono, Nur Iman (PEOPLE: International Journal of Social Sciences, 2018)
This study aims to gain a comprehensive understanding related to the correlation between political opportunity structure and the success of Temanggung tobacco peasant resistance towards government regulation 81/1999. This regulation basically obligates tobacco industries in Indonesia to standardize their cigarette product to the low tar and nicotine. As a main product of cigarette industries, kretek is the typical cigarette known as highly nicotine cigarette and mostly made from the local tobacco including Temanggung tobacco. A mutual cooperation between cigarette industries and Temanggung tobacco peasant eventually has become an economic backbone not only for tobacco peasant but also for local inhabitant generally. Feeling threatened, tobacco peasant was calling for the withdrawal and finally reach its succes after three years struggle. In order to know the correlation between two factors mentioned above, as a part of social movement theory, political opportunity approach is being used as an analytical tool. This study is also conducted by applying qualitative research methods such as interviewing actors and tracing related literatures. This research finds that there is significant correlation between the availability of political opportunity structure and the success of the resistance. Then, this study concludes that the form of the availability of political opportunity is none else than the role played by influential ally particularly local politician who closed to the national elite, the president of Indonesia republic, Megawati Soekarnoputri. Instead of its theoritical constraints, the finding strengthens a thesis that without influential ally, social movement would not be able to amplify its interests.